Total Plate Count Minuman Sari Buah yang Dijual Pedagang Kaki Lima di Kecamatan Semarang Barat - Anisa Nova Puspitaningrum; Valentina Girsang; Muhammad Ma'ruf; Fransisca Gloria; Madyo Adrianto; Cecep Sabarudin (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Microbial contamination can cause health issues that are disruptive, harmful, and potentially dangerous to health. Microbial contamination is often found in beverages widely sold on the streets, where water quality and cleanliness are often neglected. This study aims to determine the level of microbial contamination in fruit juice products sold in Semarang. The five samples used were lemon, mango, avocado, orange, and tomato juices, which were tested using the Total Plate Count method. The results of this study showed that the Total Plate Count (TPC) values of three samples such as lemon, mango, and avocado juices, did not meet the requirements of SNI 01-3719-1995. Meanwhile, two samples, orange and tomato juices, were concluded to still comply with the threshold set by SNI 01-3719-1995.